(untitled) (Research, Society and Development, 2022)
Objective: Map and categorize studies found in the literature with the themes of self-efficacy and self-concept with positive development of young people related to young basketball practitioners. Method: scoping review, with search in the WEB of SCIENCE, SCOPUS, BVS, ERIC, SportDiscus/EBSCO, REDALYC and Periódico Capes databases from 2011 onwards, considering the descriptors “basketball”, “self-efficacy”, “self- concept”, the keyword “positive Youth development”, and its correspondents in Portuguese and Spanish, using the Boolean operators “AND” and “OR”. Results: The search resulted in the selection of 8 articles regarding basketball. The articles presented the various self-efficacy, self-concept and positive development of young people, separately related to basketball, all these areas showed benefits related to the development of practitioners and not to the sport. Conclusion: different instruments were identified to measure each theme, and the lack of studies relating the three selected variables was found. This review can strengthen the importance of a sporting environment in the development of young people and the need for further studies in these areas.